2014
DOI: 10.1111/apa.12569
|View full text |Cite
|
Sign up to set email alerts
|

Population-based study shows improved postnatal growth in preterm very-low-birthweight infants between 1995 and 2010

Abstract: We demonstrated a marked decline in PNGF among preterm VLBW infants from 1995-2000 to 2006-2010. This decline was even present in extremely premature infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 26 publications
5
40
2
1
Order By: Relevance
“…In a study by Ofek Shlomai et al9), among VLBW infants born at 24- to 32-week gestational age who were discharged home at ≤40 weeks postmenstrual age, the percentage of those with severe growth failure decreased significantly from 11.5% in 1995–2000 to 5.2% in 2006–2010, and those with mild growth failure declined from 40.1% to 9.8% during these periods ( P <0.001). In a study by Cole et al10), among ELBW infants assessed at 18–22 months of corrected gestational age, 50.5% and 31.7% had weights and heights <10th percentile at follow-up, respectively.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In a study by Ofek Shlomai et al9), among VLBW infants born at 24- to 32-week gestational age who were discharged home at ≤40 weeks postmenstrual age, the percentage of those with severe growth failure decreased significantly from 11.5% in 1995–2000 to 5.2% in 2006–2010, and those with mild growth failure declined from 40.1% to 9.8% during these periods ( P <0.001). In a study by Cole et al10), among ELBW infants assessed at 18–22 months of corrected gestational age, 50.5% and 31.7% had weights and heights <10th percentile at follow-up, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Among VLBW infants of 24–32 weeks' gestational age who were discharged at ≤40 weeks postconception age (PCA), the percentage of those with severe growth failure has decreased significantly, from 11.5% in 1995–2000 to 5.2% in 2006–2010, and mild growth failure declined from 40.1% to 9.8% during these periods; however, these improvements remain insufficient9).…”
Section: Introductionmentioning
confidence: 99%
“…37 Improvement in postnatal growth in very low birth weight preterm infants in Israel may play a role in decreasing mortality and morbidity including ROP. 38,39 Severe postnatal growth failure decreased from 11.7% in 1995-2000 to 7.2% in 2001-2005 and 5.2% in 2006-2010. A study of 317 very low birth weight preterm babies revealed that low weight gain by 6 weeks of life was an important and independent risk factor for severe ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Growth z ‐scores were calculated at birth, at the beginning of the study, and at the end of the study using the LMS method, based on Fenton growth charts . EUGR was defined as a decrease of >1 z ‐score (severe EUGR >2) in weight between birth and other measures taken during the hospital stay …”
Section: Methodsmentioning
confidence: 99%